Theoretical Insight on the Formation Mechanism of a Trisubstituted Derivative of Closo-Decaborate Anion [B10H7O2CCH3(NCCH3)]0 - Ilya N. Klyukin; Anastasia V. Kolbunova; Alexander S. Novikov; Andrey P. Zhdanov; Konstantin Yu. Zhizhin; Nikolay T. Kuznetsov (Inorganics, 2023)
A theoretical modelling of the interaction process between a protonated complex of carboxonium derivative [2,6-B10H8O2CCH3*Hfac]0 and acetonitrile molecule CH3CN was carried out. As a result of the process, a trisubstituted [B10H7O2CCH3(NCCH3)]0 derivative was formed. This reaction has an electrophile-induced nucleophilic substitution (EINS) mechanism. The main intermediates and transition states of the substitution process were established. As in the case of all previously investigated EINS processes, the key intermediate was an anion with a dihydrogen H2 fragment attached to one boron atom (B(H2) structure motif). The process of nucleophilic substitution can proceed on a different position of the cluster cage. The main potential pathways were assessed. It was established that substitution on the B4 position of the cluster cage was the most energetically favourable, and the [2,4,6-B10H7O2CCH3(NCCH3)]0 isomer was formed.